1997
DOI: 10.1007/pl00004944
|View full text |Cite
|
Sign up to set email alerts
|

The role of vasopressin on the effect of U-50,488 to block the development of morphine tolerance and physical dependence

Abstract: U-50,488, a selective kappa-opioid receptor agonist, has been reported to inhibit the development of antinociceptive tolerance to morphine in mice, rats and guinea pigs, but the mechanism involved in this action remains unknown. Since U-50,488 has been reported to suppress the plasma vasopressin level, we investigated the role of vasopressin with U-50,488 in the male Sprague Dawley rat in this study. Animals (230-270 g) were chronically treated with morphine (10 mg/kg, i.p.) twice a day for 6 days in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…U‐50,488 ( trans ‐3,4‐dichloro‐N‐methyl‐N‐[2‐(1‐pyrrolidinyl)‐cyclohexyl]‐benzeneacetamide hydrochloride), a selective K ‐opioid receptor agonist, has been shown to suppress the development of antinociceptive tolerance to morphine in rats (Yamamoto et al , 1988), mice (Takahashi et al , 1991) and guinea‐pigs (Tao et al , 1994). The mechanism may involve the activation of K ‐opioid receptors and an inhibitory effect of U‐50,488 on vasopressin release (Tao et al , 1997). Xu et al (1992) demonstrated that concomitant intracerebroventricular (i.c.v.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…U‐50,488 ( trans ‐3,4‐dichloro‐N‐methyl‐N‐[2‐(1‐pyrrolidinyl)‐cyclohexyl]‐benzeneacetamide hydrochloride), a selective K ‐opioid receptor agonist, has been shown to suppress the development of antinociceptive tolerance to morphine in rats (Yamamoto et al , 1988), mice (Takahashi et al , 1991) and guinea‐pigs (Tao et al , 1994). The mechanism may involve the activation of K ‐opioid receptors and an inhibitory effect of U‐50,488 on vasopressin release (Tao et al , 1997). Xu et al (1992) demonstrated that concomitant intracerebroventricular (i.c.v.)…”
Section: Introductionmentioning
confidence: 99%
“…with morphine (i.p.) blocked the development of morphine tolerance in rats (Tao et al , 1997). Recently, both competitive and non‐competitive N‐methyl‐D‐aspartate (NMDA) antagonists (Trujillo & Akil, 1991; Marek et al , 1991; Tiseo & Inturrisi, 1993), and nitric oxide synthase inhibitors (Kolesnikov et al , 1992; Majeed et al , 1994) have been found to prevent the development of morphine tolerance, suggesting that the development of morphine tolerance may also involve the activation of NMDA receptors and NO production.…”
Section: Introductionmentioning
confidence: 99%